Control en la administración para una información financiera confiable - Martín Granados, Victoria María Antonieta; Mancilla Rendón, María Enriqueta (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
The financial information is the document that the administration of a juridical entity issues to know his financial situation. The financial information is useful and confiable for the users of the financial information when this has been prepared under conditions of certainty. This certainty is provided by the administration when it establishes political and procedures of internal control, as well as the surveillance in the accomplishment of the internal control. This control incides in the financial information since it is inherent to the operative flow and extends itself in relevant information, veracious and comparable. This is important for users of the financial information, due to the fact that they take timely and objective decisions.

La información financiera es el documento que la administración de una entidad jurídica emite para dar a conocer su situación financiera. Esta es útil y confiable para los usuarios cuando es preparada bajo condiciones de certeza. La seguridad de que esta sea un documento confiable la proporciona la administración cuando establece políticas y procedimientos de control interno, así como su cumplimiento. A su vez, el control interno incide en la información financiera ya que es inherente al flujo operativo y trasciende en información relevante, veraz y comparable, lo cual es importante para los usuarios de la información financiera, pues les permite tomar decisiones oportunas y objetivas.
Management Control for Reliable Financial Information
Keywords: Control interno; Información financiera contable; https://purl.org/pe-repo/ocde/ford#5.02.04